The "Good" Schools: Academic Performance Data, School Choice, and Segregation - David M. Houston; Jeffrey R. Henig (SAGE Publishing, 2023)
We examine the effects of disseminating school-level academic performance data-achievement status, achievement growth, or both-on parents' school choices and their implications for racial, ethnic, and economic segregation. Many researchers consider growth to be a superior (if still imperfect) measure of school effectiveness relative to status. Moreover, compared to status, growth has weaker relationships with schools' demographic compositions. We conduct an online survey experiment featuring a nationally representative sample of parents and caretakers of children ages 0-12. Participants choose between three randomly sampled elementary schools drawn from the same school district. The provision of status information guides participants toward schools with higher achievement status and fewer Black, Hispanic, and economically disadvantaged students. The provision of growth information and the provision of both types of academic performance data guide participants toward higher growth schools. However, only growth information-alone, and not in concert with status information-tends to elicit choices with desegregating consequences.